Gestión de los residuos de poda: experiencias en el periurbano del AMBA - Cuellas, Marisol Virginia (2023)
The comprehensive management of urban solid waste is an essential tool to mitigate and minimize the environmental impact caused by human activity in a city. In the maintenance of green areas, tree pruning generates a large volume of organic waste. In general, this type of waste, if not managed correctly, can cause environmental problems such as micro-gardens and fire risk, among others. One of the management possibilities is chipping, which reduces its size and generates materials with great potential for use by transforming them into other products that allow their reincorporation into the production cycle, thus reducing the extraction of raw materials and natural resources provided by the ecosystem. This proposal through technical cooperation (between INTA and the Municipality) seeks to form a work network that allows the care of the environment, through the strengthening of family producers in the region, generating tools to produce sustainably.